2014
DOI: 10.3389/fchem.2014.00057
|View full text |Cite
|
Sign up to set email alerts
|

Bimodular high temperature planar oxygen gas sensor

Abstract: A bimodular planar O2 sensor was fabricated using NiO nanoparticles (NPs) thin film coated yttria-stabilized zirconia (YSZ) substrate. The thin film was prepared by radio frequency (r.f.) magnetron sputtering of NiO on YSZ substrate, followed by high temperature sintering. The surface morphology of NiO NPs film was characterized by atomic force microscope (AFM) and scanning electron microscope (SEM). X-ray diffraction (XRD) patterns of NiO NPs thin film before and after high temperature O2 sensing demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…for comparison. Besides the absorption bands of Fe 3 O 4 @PPY, which have been described previously , the stretching shoulder band and bending vibration band of NiO were, respectively, observed at 626 and 562 cm −1 indicating the presence of NiO on the surface of the support .…”
Section: Resultssupporting
confidence: 72%
“…for comparison. Besides the absorption bands of Fe 3 O 4 @PPY, which have been described previously , the stretching shoulder band and bending vibration band of NiO were, respectively, observed at 626 and 562 cm −1 indicating the presence of NiO on the surface of the support .…”
Section: Resultssupporting
confidence: 72%
“…Nickel oxide NiO (Sun et al, 2014 ) is a significant p-type semiconductor, and has been widely used as catalyst (Yu et al, 2015 ), lithium-ion battery (Gu et al, 2016 ; Long et al, 2018 ), gas sensor (Wang et al, 2016 ; Zhou et al, 2018b ), magnetic material (Cui et al, 2011 ), and so on. In recent years, many researchers have reported that NiO can be applied to fabricate high performance gas sensors for detecting some special gases such as hydrogen (Sta et al, 2016 ), NO 2 (Hoa and El-Safty, 2011 ), ethanol (Miao et al, 2017 ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…3c and d . 23 No diffraction line observed for PPY because of the amorphous nature of this compound. 24 The average particle sizes of Fe 3 O 4 , NiO and NiS were calculated by Scherrer's equation.…”
Section: Characterization Of the Synthesized Photocatalystsmentioning
confidence: 99%